1979
DOI: 10.1111/j.1346-8138.1979.tb01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological Studies on Psoriasis

Abstract: In vivo deposits of fibrin, fibrinogen, plasminogen, complements and immunoglobulins were observed using immunofluorescent (IF) staining of psoriatic lesions. Deposits of fibrin were seen in either the horny layer or the dermal papillae. A linear cytoplasmic appearance of fluorescence in the psoriatic scales was a common pattern of the staining. "IFstaining of the psoriatic horny/layer for fibrinogen and plasminogen' yielded essentially the same pattern as those of fibrin and IgG.These findings suggest that so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been reported that IgA bearing lymphoid cells are significantly increased in peripheral blood (25) and that IgA and IgG IC are highly detectable in serum of psoriatic pa路 tients (26,27). It has been demonstrated that IgM and IgG IC, fibrinogen and/or fibrin, and plasminogen are also deposited at vessels and the D-Ejunction of psoriatic lesions (28)(29)(30).…”
Section: Iffindings In the Upper Dermismentioning
confidence: 99%
“…Furthermore, it has been reported that IgA bearing lymphoid cells are significantly increased in peripheral blood (25) and that IgA and IgG IC are highly detectable in serum of psoriatic pa路 tients (26,27). It has been demonstrated that IgM and IgG IC, fibrinogen and/or fibrin, and plasminogen are also deposited at vessels and the D-Ejunction of psoriatic lesions (28)(29)(30).…”
Section: Iffindings In the Upper Dermismentioning
confidence: 99%